Oral Supplementation with Baker's Yeast Beta Glucan Is Associated with Altered Monocytes, T Cells and Cytokines following a Bout of Strenuous Exercise - McFarlin, Brian K.; Venable, Adam S.; Carpenter, Katie C.; Henning, Andrea L.; Ogenstad, Stephan (Frontiers in Physiology, 2017)
Exercise and physical labor in extreme environmental conditions causes transient decreases in immune cell and cytokine concentrations, likely increasing the susceptibility to opportunistic infection. Baker’s yeast beta glucan (BYBG) has been previously demonstrated to be an effective countermeasure in athletes, but its effectiveness in individuals of average fitness under similar physical stress is unknown. The purpose of this study was to determine if 10 days of oral supplementation with BYBG could modify previously observed suppression of monocytes, T cells, circulating and whole blood LPS-stimulated cytokines due to strenuous exercise. Venous blood samples were collected from 109 healthy volunteers prior to, immediately after, 2h, and 4h post-exercise. Monocyte and T cell concentration, cell-surface receptor expression and serum and LPS-stimulated cytokines were assessed. BYBG significantly (P<0.05) altered total and classic monocyte concentration and expression of CD38, CD80, CD86, TLR2, and TLR4 on monocyte subsets. BYBG also significantly increased CD4+ and CD8+ T cell concentration and the exercise response of CCR7+/CD45RA- central memory (TCM) cells. Likewise, BYBG significantly (P<0.05) altered serum IFN- and IL-2, and LPS-stimulated IFN-, IL-2, IL-4, and IL-7. Taken together these data support the hypothesis that oral BYBG supplementation modulates the expected exercise response for individuals of average fitness. This may result in a decrease in susceptibility to opportunistic infections after strenuous exercise.